EDUCATIONAL IDEOLOGY IN INDIGENOUS MUSLIM COMMUNITIES: Emancipation, Environmental Stewardship, and Food Sovereignty - Hery Wibowo; Muhammad Fadhil Nurdin; Desi Yunita; Kartini Kamaruzzaman; Elsa Lutmilarita Amanatin (Journal of Contemporary Islam and Muslim Societies, 2026)
This study examines the ideological orientations shaping indigenous education in the context of environmental protection and food security amid deepening marginalization. The research employs a mixed-methods design, combining William O’Neill’s Educational Ideology Questionnaire with qualitative observations and in-depth interviews. The findings reveal that indigenous education actors predominantly adopt conservative and intellectualist orientations, emphasizing the preservation of customary values, ecological balance, and structured knowledge transmission. Institutional practices, however, reflect more liberal tendencies, prioritizing inclusivity and adaptive learning. This interplay of ideologies positions education as both contextual and emancipatory, reinforcing indigenous agency in advancing ecological resilience, food sovereignty, and social justice.Keywords: environmental protection; food security; educational ideology; indigenous peoples